Actividad con escritores. (UNED, 2025)
Mesa principal, grupo mediano de personas con Joaquín Calvo, Guido Miranda, Adelita Sibaja, Eugenio Rodríguez, Rodrigo Arias, Alberto Cañas, Luis Ferrero, Rodrigo Alberto Carazo Zeledón.